Avaliação de fatores de risco associados à demência e comprometimento cognitivo não demência em uma população de idosos da cidade de Caeté - MG (Estudo Pietá) - Vivian Proenca Lara (2012)
Neurodegenerative disorders, such as cognitive impairment and dementia, emerge as consequences of aging. With the aim of evaluating the factors which lead to a healthy cerebral aging, it was accomplished, in the city of Caeté MG, the Pietà Study, an epidemiological survey with the population aged 75 years or more. Three hundred and nine elderly subjects enrolled in this study were divided in three groups: controls (n=158), cognitive impairment no-dementia (CIND) (n=92) and dementia (n=59), so as to investigate and compare socio-demographic, clinical and laboratory parameters. The individuals were interviewed, went through clinical and neurological examination and had blood samples taken. Results show that levels of serum cortisol were higher in dementia group, intermediate in CIND group and lower in control group. Significant differences were observed between control and CIND groups (p=0.003), control and dementia (p=0.001), but not between CIND and dementia (p=0.269). These results suggest that the increase in hormone levels can be either cause or consequence of hippocampal damage. Significant differences among groups (p<0.05) were also observed for the following parameters: age, civil status, ankle-brachial index and polymorphism frequencies of APOE gene. Gender, educational level, socio-economic status, body mass index, blood pressure, diagnosis of diabetes mellitus and lipid profile did not show any differences (p>0.05) when the three groups were compared. According to multivariate analyses, higher cortisol levels, lower HDL-c and triglycerides, APOE 34/44 genotypes, aging and civil status: never-married or widows/separated/divorced individuals were all independently associated with the risk of developing CIND/dementia. Therefore this study identifies risk factors associated with the development of CIND/dementia, which can be a starting point for actions that minimize their effects, so that more individuals can go through aging with their cognitive function preserved.